2000
DOI: 10.2307/3870925
|View full text |Cite
|
Sign up to set email alerts
|

The Cochliobolus Carbonum SNF1 Gene Is Required for Cell Wall-Degrading Enzyme Expression and Virulence on Maize

Abstract: The production of cell wall-degrading enzymes (wall depolymerases) by plant pathogenic fungi is under catabolite (glu-cose) repression. In Saccharomyces cerevisiae , the SNF1 gene is required for expression of catabolite-repressed genes when glucose is limiting. An ortholog of SNF1 , ccSNF1 , was isolated from the maize pathogen Cochliobolus car-bonum , and ccsnf1 mutants of HC toxin-producing (Tox2) and HC toxin-nonproducing (Tox2) strains were created by targeted gene replacement. Growth in vitro of the ccsn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 0 publications
7
105
2
1
Order By: Relevance
“…Similarly, the cutinase gene (CutAb) had 73-times fewer transcript in the ∆abvf19 mutant in this study, but cutab mutants in Yao and Kӧller's did not affect virulence (Yao and Köller, 1995). These mutation studies suggested that each enzyme-coding gene either contributed little to virulence, or their functions were redundant as proposed previously based on ccSNF1 and foSNF1 studies (Ospina-Giraldo et al, 2003;Tonukari et al, 2000). The current ∆abvf19 mutant study supports the importance of coordinated regulation of those genes during pathogenesis.…”
Section: Importance Of a Coordinated Expression Of Individual Genessupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly, the cutinase gene (CutAb) had 73-times fewer transcript in the ∆abvf19 mutant in this study, but cutab mutants in Yao and Kӧller's did not affect virulence (Yao and Köller, 1995). These mutation studies suggested that each enzyme-coding gene either contributed little to virulence, or their functions were redundant as proposed previously based on ccSNF1 and foSNF1 studies (Ospina-Giraldo et al, 2003;Tonukari et al, 2000). The current ∆abvf19 mutant study supports the importance of coordinated regulation of those genes during pathogenesis.…”
Section: Importance Of a Coordinated Expression Of Individual Genessupporting
confidence: 61%
“…The importance of CWDE genes in virulence has been supported by identification of mutants with impaired derepression mechanisms of carbon catabolite repression in Colletotrichum carbonum and Fusarium oxysporum (Ospina-Giraldo et al, 2003;Tonukari et al, 2000).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In other cases, multiple-gene disruption failed to significantly decrease virulence (8,12,13). Therefore, conclusive evidence for or against a role for any particular enzyme activity in any aspect of pathogenesis has been difficult to obtain (51). A major decrease in virulence would require disruption of genes that encode all of the functionally redundant barrierdegrading enzymes that can play an essential role in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other information that can be obtained from such question includes the length of the protein, its hydrophobic/hydrophilic nature, subcellular localization, presence/absence of signal peptide, and motifs (Tonukari et al, 2000). Faculty can benefit twice from the time spent preparing for class when they write test questions that require students to access genomic data related to their research.…”
Section: Bioinformatics and Genomicsmentioning
confidence: 99%